2018
DOI: 10.1093/intqhc/mzx190
|View full text |Cite
|
Sign up to set email alerts
|

Patient and hospital characteristics that influence incidence of adverse events in acute public hospitals in Portugal: a retrospective cohort study

Abstract: ObjectiveTo analyse the variation in the rate of adverse events (AEs) between acute hospitals and explore the extent to which some patients and hospital characteristics influence the differences in the rates of AEs.DesignRetrospective cohort study. Chi-square test for independence and binary logistic regression models were used to identify the potential association of some patients and hospital characteristics with AEs.SettingNine acute Portuguese public hospital centres.ParticipantsA random sample of 4250 cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 29 publications
2
39
1
11
Order By: Relevance
“…Nevertheless, this situation must be carefully analyzed because these results may reflect a real increase in the in-hospital ADE frequency, but they may also be associated with greater awareness of hospitals about the patients' safety and, subsequently, better practice regarding the recording and encoding of these events. In a study carried out at nine Portuguese acute care hospital centers 9 , it was observed that the adverse event frequency was higher in the accredited hospitals (13.7% vs. 11.2%). A reasonable explanation for these results, according to the authors, may be associated with the fact that the accredited hospitals display a greater awareness of the patient's safety and have a systemic practice of data recording and analysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, this situation must be carefully analyzed because these results may reflect a real increase in the in-hospital ADE frequency, but they may also be associated with greater awareness of hospitals about the patients' safety and, subsequently, better practice regarding the recording and encoding of these events. In a study carried out at nine Portuguese acute care hospital centers 9 , it was observed that the adverse event frequency was higher in the accredited hospitals (13.7% vs. 11.2%). A reasonable explanation for these results, according to the authors, may be associated with the fact that the accredited hospitals display a greater awareness of the patient's safety and have a systemic practice of data recording and analysis.…”
Section: Discussionmentioning
confidence: 98%
“…In Portugal, the evidence available also points to a high rate of in-hospital ADEs. A study carried out in nine acute care public hospital centers, using the clinical record review methodology, identified an incidence of 12.5% adverse events in the year 2013, of which 9.8% were associated with drug errors, representing the third most frequent adverse event 9 . According to other studies carried out in Portuguese public hospitals, using administrative data, 1.46% and 1.88% of hospitalized patients showed at least one ADE 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Bilingual hospitals also had a higher rate of harm overall than English-speaking hospitals. This could be due to the fact that a greater proportion of bilingual hospitals are academic institutions, which generally have a higher rate of harm [49,50]. While this could provide an explanation for the…”
Section: Discussionmentioning
confidence: 99%
“…Zbog svega toga preporuča se ostaviti hospitalizaciju samo za slučajeve kada ambulantno liječenje ne daje rezultate, jer svaki dolazak bolesnika s demencijom u bolnicu otvara mogućnosti neželjenih događaja (2,4,(13)(14)(15)(16).…”
Section: Discussionunclassified
“…Due to all these reasons, it is recommended to consider hospitalization only in cases where outpatient treatment does not produce results, as each hospital admission of patients with dementia increases the risk of adverse events (2,4,(13)(14)(15)(16).…”
Section: Zaključakmentioning
confidence: 99%